2014
DOI: 10.1080/09658211.2013.872278
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of alcohol and eye movements on cross-race face learning

Abstract: This study examines the impact of acute alcohol intoxication on visual scanning in cross-race face learning. The eye movements of a group of white British participants were recorded as they encoded a series of own-and different-race faces, under alcohol and placebo conditions. Intoxication reduced the rate and extent of visual scanning during face encoding, reorienting the focus of foveal attention away from the eyes and towards the nose. Differences in encoding eye movements also varied between own-and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
3
24
2
Order By: Relevance
“…We can only speculate as to why the nose area rather than the hair region was the focus of the alcohol group's gaze in this earlier study but the first important point to note is that shifts in eye movements and shifts in attention can dissociate such that eye fixations to a particular stimulus feature do not guarantee the viewer is necessarily attending to that feature (Posner, 1980). But if we assume that eye fixations are a reliable proxy for the focus of overt attention, then one possibility is that Harvey's (2014) stimulus faces had a less diverse range of hairstyles than those of the present study. This would reduce the likelihood of alcohol participants being distracted by the hairstyle of each stimulus face.…”
Section: Discussionmentioning
confidence: 90%
“…We can only speculate as to why the nose area rather than the hair region was the focus of the alcohol group's gaze in this earlier study but the first important point to note is that shifts in eye movements and shifts in attention can dissociate such that eye fixations to a particular stimulus feature do not guarantee the viewer is necessarily attending to that feature (Posner, 1980). But if we assume that eye fixations are a reliable proxy for the focus of overt attention, then one possibility is that Harvey's (2014) stimulus faces had a less diverse range of hairstyles than those of the present study. This would reduce the likelihood of alcohol participants being distracted by the hairstyle of each stimulus face.…”
Section: Discussionmentioning
confidence: 90%
“…While findings from line-up studies suggest that intoxication at the time of witnessing (i.e. encoding) a target face does not impair subsequent identification performance, two standard old-new face recognition studies have shown alcohol impairments (Harvey 2014 ; Hilliar et al 2010 ). In an investigation of the effect of alcohol intoxication on the own-race (unfamiliar) face recognition bias (ORB), Hilliar et al ( 2010 ) reported higher false identification rates and lower hit rates for intoxicated participants relative to sober controls, particularly for own-race faces.…”
mentioning
confidence: 99%
“…When the face is the only or key stimulus, however, it is more difficult to predict alcohol’s effect according to AMT, as it is not straightforward which area of a face is considered salient or central in a given context. At the time of writing this manuscript, the authors are aware of only two studies which have tested alcohol effects in a face memory task with respect to AMT (Colloff and Flowe 2016 ; Harvey 2014 ). Colloff and Flowe ( 2016 ) found no support for AMT in their study which tested the effect of alcohol and salient facial characteristics on face memory.…”
mentioning
confidence: 99%
“…For example, whereas some researchers choose written retrieval tasks , others use live mock interviews in which participants answer free, cued, multiple choice and/or yes/no questions provided by an interviewer . Identification procedures consist of showups , simultaneous lineups or face recognition paradigms (Colloff & Flowe, 2016;Harvey, 2014;Hilliar, Kemp, & Denson, 2010). The data from these interviews and identifications are then compared to determine how alcohol affects witness memory.…”
Section: Alcohol and Eyewitness Memorymentioning
confidence: 99%
“…The participant's task during the second viewing is to state whether each face displayed is old or new. Findings from these studies are mixed because one study suggested that intoxicated participants recognized fewer old faces than those in the placebo and control conditions (Hilliar et al, 2010), while other studies suggest that alcohol has no effect on the ability of participants to remember old and new faces (Colloff & Flowe, 2016;Harvey, 2014).…”
Section: Memory For Faces Researchers Examining the Effects Of Alcohmentioning
confidence: 99%